Laporan kajian kepuasan pengguna Perpustakaan Universiti Malaya 2008 - Koh, A.P.; Hazidah, N.A. (University of Malaya Library, 2008)
The Library User Survey 2008 was carried out from 16 October to 15 November 2008. A questionnaire was designed and distributed to users online via UM e-survey and manually within the library. Users were asked to evaluate the collection, facilities/services and staff of the library. More than 1400 questionnaires were collected and analysed using SPSS version 17.00.